Knowledge and Practice About Blood Pressure Measurement in Children: Healthcare Provider’s Perspective: Knowledge About Blood Pressure Measurement - Sultana, Azmeri; Afroze, Sharmin; Sonia, Sheikh Farjana; Qader, Md. Abdul; Rumana, Jubaida; Khanam, Morsheda; Iman, Kazi; Rashid, Ismail Ibne; Hanif, Mohammed (Journal of Pediatric Nephrology, 2023)
Background and Aim: Hypertension (HTN) has become more prevalent among youngsters. It is frequently under-recognized due to a lack of routine blood pressure measurement in many health centers, partly owing to a shortage of devices and possibly because of the notion that it is not the foremost disease in children. In Bangladesh, there is a scarcity of data on how doctors view childhood HTN and their practice of measuring blood pressure in children. Methods: This cross-sectional mailed-based survey was done on pediatricians and approved by the institutional review board of Dr. Khan Shishu Hospital & the Institute of Child Health from June to December 2021. We obtained the email addresses of all pediatricians from the Bangladesh Pediatric Association. Results: Of the 536 pediatricians in the mailing sample, 257 cases responded and the response rate was 47.9%. The majority of respondents (62.4%) were general pediatricians and only 12.2% were pediatric nephrologists. This survey revealed that 77.2% of pediatricians did not measure blood pressure routinely among children 3-18 years of age, whereas 66% reported measuring blood pressure if children had risk factors. Conclusion: The findings of our study point to a knowledge and practice gap among pediatricians, who are primary health care providers, when diagnosing hypertension in children. For children aged 3 to 18 years, most pediatricians reported no regular assessment of blood pressure. Most pediatricians did not repeat blood pressure measurements for diagnosis, nor did they often use blood pressure cuffs or charts for children. These issues need to be addressed for better diagnosis and treatment of childhood HTN.